RELIGIOUS MODERATION IN AN EASTERN JAVANESE TOWN - Syaifudin Zuhri (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2022)
This article is a result of a massive survey conducted in Tulungagung, a south-eastern Javanese middle town in the early 2022. The survey involves 2569 data collectors that successfully, following a series of data cleansing, reported refined 7140 data survey. The article is a descriptive analytic which shows the views of respondents of the survey. They are leaders in many Javanese villages in the city which include religious leaders (RL), leaders of community (LC), and young leaders (YL). The survey addresses four important issues that have been officially recognised as the official four pillars of religious moderation (moderasi beragama), namely commitment for Indonesian nationalism, tolerance, anti-violence, acceptance to local cultures. The survey finds that there has been no worrying indicator threatening the four pillars of moderasi beragama and argues that a challenge for religious pluralism in contemporary Java lies at the coexistence between groups within the same religion. It also suggests that “moderating the moderate” has been a key challenge for the state’s initiative of moderasi beragama, otherwise the project becomes obsolete.